Altered brain metabolism in vestibular migraine: Comparison of interictal and ictal findings. (January 2014) - Shin, Jung H; Kim, Yu K; Kim, Hyo-Jung; Kim, Ji-Soo
Background: Vestibular symptoms/signs frequently coexist with migraine, but the mechanisms of migraine-related vestibular dysfunction remain to be elucidated. This study aimed to determine altered brain metabolism in vestibular migraine. Methods: Two patients with vestibular migraine underwent 18 F-fluorodeoxy glucose (FDG) positron-emission tomography (PET) during and between attacks of vestibular migraine in addition to detailed neurotological evaluation. We analyzed the regional brain metabolism of the patients in comparison with that of age-matched healthy controls in each patient. We also compared ictal with interictal FDG PET using a subtraction method. Results: During the attacks, both patients showed an activation of the bilateral cerebellum and frontal cortices, and deactivation of the bilateral posterior parietal and occipitotemporal areas. One patient also showed hypermetabolism in the dorsal pons and midbrain, right posterior insula, and right temporal cortex while the other patient had an additional activation of the left temporal cortex. Compared with interictal images, ictal PET showed increased metabolism in the bilateral cerebellum, frontal cortices, temporal cortex, posterior insula, and thalami. Conclusion: During the attacks of vestibular migraine, the increased metabolism in the temporo-parieto-insular areas and bilateral thalami indicates activation of the vestibulo-thalamo-cortical pathway, and decreased metabolism in the occipital cortex may represent reciprocal inhibition between the visual and vestibular systems.